PENGEMBANGAN METODE EDUKASI TEMAN SEBAYA TERHADAP PENINGKATAN PENGETAHUAN GIZI REMAJA SMA DI WILAYAH KOTA MALANG - Pudji Suryani (Jurnal Informasi Kesehatan Indonesia (JIKI), 2022)
Low nutritional knowledge will have an impact on balanced nutrition attitudes and behavior in adolescents, so that the peer educator approach is expected to convey nutritional information and change the knowledge and behavior of their peers to be healthier. From peer education methods, it needs to be developed to measure the effectiveness of educational methods. The research design used was a pre-experimental design, namely one group pre-test post-test. The target population of the study were female high school students of class XII at MA Nurul Ulum. The results showed that in groups 1 to 3 showed a significant value of less than 0.05, which means that there is a difference in knowledge before and after the intervention through peer education. Meanwhile, groups 4 and 5 showed a significance value of more than 0.05, which means that there was no difference in knowledge before and after the intervention through peer education in Senior High School girls about adolescent nutrition. It can be concluded that the results of this study indicate that the development of peer education methods is effective in increasing the nutritional knowledge of Senior High School girls up to group 3. The general conclusion of this research is the development of an effective peer education method for increasing the nutritional knowledge of adolescent girls up to group 3 (3 levels) at MA Nurul Ulum Malang City. Keywords: peer education, nutrition, youth